APLIKASI METODE MAGNETIK UNTUK MELOKALISASI TARGET ZONA MINERALISASI EMAS DI DAERAH “X” - Seftyand S Briyantara; Tony Yulianto (Youngster Physics Journal, 2015)
This research aimed to localize the target of the gold mineralized zones are located in “X” area. Based on the evaluation of geological data mineral alteration, lithology, and geology structure, this area is concluded that the mineralization type was High Sulphidation with characteristic alteration found in the form of quartz, phyropilite, allunite, muscovite, smectite and kaolinite.The methods are processing data using Oasis Montaj software which then created the total magnetic intensity map. Of the total magnetic intensity map was filtered to produce 50 meters upward continuation and RTP (reduction to the pole) map. Qualitative interpretation were done by analysis of RTP map to determine the target of gold mineralization according to the characteristic of magnetic anomaly. Quantitative interpretation was done by combined between RTP map with IP data. Besides that, quantitative interpretation was done by 2D modelling by slicing RTP map using Oasis Montaj.The result of study showed two high anomalies can be interpreted as igneous intrusions with susceptibility 1 x 10-2 (SI-unit) and two low anomalies with susceptibility -3.7 x 10-5 (SI-unit) can be interpreted as the mineral quartz. Keywords: gold, minerals alteration, reduce to the pole, high sulphidation, oasis montaj.